Identidades e espacialidades do Cariri: um estudo sobre o podcast Budejo - Oliveira, Alessandra Caroline Luciano Vital Monteiro de (2024)
This research aims to analyze how the Budejo podcast presents Cariri to its listeners through thematic episodes of the program about the region. The theoretical framework is based on the proposals on mediations by Jesús Martín-Barbero (2008), specifically taking into account the notions of technicalities, identities and spatialities involved in the production and product of the communicative process established from the podcast in question. Taking a historical approach to podcasts, we rely on authors such as Luiz and Assis (2010); Vicente (2018); Avelar, Prata and Martins (2018); Viana (2020); and Bonini (2020). In developing the mediation proposals adopted for the research, we resorted to Maffesoli (2004); MartínBarbero (2006; 2008; 2009; 2018); Santos (2006); Orozco Gómez (2006); Haesbert (2007); Ronsini (2010); Escosteguy and Sifuentes (2016); Bufarah (2020); Viana and Chagas (2021). The methodological process supports the theoretical-methodological perspective of the theory of mediations and adopts the modes of addressing as the methodological concept (Ellswoarth, 2001), using the analysis operators of thematic organization, mediators, social role and technical resources. Throughout the episodes analyzed, we demonstrate how Budejo explores aspects linked to identities in their religious, political, social, cultural, economic, natural diversity, among others – and to spatialities, especially relating to inhabited space (MartínBarbero, 2018).